Automated Grading and Feedback Systems: Reducing Teacher Workload and Improving Student Performance (Journal of Asian Development Studies, 2024)
With rising expectations on teacher workload as a result of grading and providing feedbackthe innovative use of automated grading is a possible solution. Such systems are designed tomake grading systems more efficient in the same regard as increasing students’ interest. In thisresearch, the effect of automated grading and feedback on the reduction of teacher burden andenhancement of students’ performance is critically analyzed, and recommendations, based onthe findings of this study, for educators, as well as policymakers, implementing the technologieswill be provided. An exploratory technique was followed for the study and both quantitativedata were collected through classroom observation both prior to as well as post integration ofautomated grading systems. For instance, the teacher grading hours and the percentage of thestudents completing the assignments were included as main measures besides the classroomparticipation rate. The results present a clear picture of the fact that grading time reduces andwas found to have reduced from 15hrs per week to 9.75hrs per week – a reduction of 35%.Also, there was a significant enhancement in students’ interaction; while assignmentsubmission rates went up from 70% to 88% and class contribution from 65% to 81%. The useof automated grading and feedback systems is the utilization of the best strategies because itrelieves the teacher of so much work as well as makes the students be more focused andinterested in their work. These studies should be seen as an opportunity for the developmentand implementation of such technologies because of the demonstrated ability of the giventechnologies to change the practices of education and enhance learning achievement.